Effects of Both Preemption and Entrenchment in the Retreat from Verb Overgeneralization Errors: Four Reanalyses, an Extended Replication, and a Meta-Analytic Synthesis - Ben Ambridge; Libby Barak; Elizabeth Wonnacott; Colin Bannard; Giovanni Sala (Collabra: Psychology, 2018)
How do speakers avoid producing verb overgeneralization errors such as *'She covered paint onto the wall' or *'She poured the cup with water'? Five previous papers have found seemingly contradictory results concerning the role of 'statistical preemption' (competition from acceptable alternatives such as 'She covered the wall with paint' or 'She poured water into the cup') and 'entrenchment' (a mechanism sensitive to all uses of the relevant verb). Here, we use more appropriate measures of preemption and entrenchment (attraction measures based on the chi-square statistic, as opposed to using only the frequency of occurrence in favoured constructions) as well as more appropriate statistical analyses and, in one case, a larger corpus to reanalyse the data from these studies. We find that for errors of verb argument structure overgeneralization (as in the examples above), preemption/entrenchment effects are almost always observed in single-predictor models, but are rarely dissociable, due to collinearity. Fortunately, this problem is much less acute for errors of reversative 'un'- prefixation (e.g., *'unsqueeze'; *'uncome'), which could in principle be blocked by (a) non-reversative uses of the same verb root (e.g., 'squeeze', 'come'; entrenchment), and/or (b) lexically-unrelated verbs with similar meanings to the relevant 'un'- forms (e.g., 'release', 'go'; preemption). Across a reanalysis of two previous studies of 'un'- prefixation, and a new extended replication with adults, we find dissociable effects of both preemption and entrenchment. A meta-analytic synthesis revealed that, across the studies, both effects are reliable, though preemption appears to increase with age. We conclude that a successful account of the retreat from verb overgeneralization is likely to be one that yields preemption and entrenchment as effects that fall naturally out of the learner’s attempts to communicate meaning, rather than one that treats these effects as mechanisms in their own right, and discuss current accounts that potentially meet this criterion. Finally, we set out some methodological recommendations that can be profitably applied not only to corpus-based experimental studies, but studies of child language acquisition in general.